A Research on the Concept of Relationship Marketing Approach and Customer Buyer/Purchase Behavior in FMCG: Exploring the Impact of Relationship Marketing on Buyer Behavior in the FMCG Industry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Relationship marketing rose with regards to service marketing, however as of late its degree extended to the point where various creators think of it as another worldview of marketing applicable for any organization in a market. In particular, enthusiasm for relationship ideas has been developing among producers of quick moving consumer merchandise who attempt to defeat the constraints of conventional mass marketing approaches. Notwithstanding, as opposed to the predominant Howard-Sheth hypothesis of consumer buyer behavior, the NBD-Dirichlet hypothesis of purchase behavior predicts that, when continue buying behavior wins, such relationship marketing strategies won't fill in true to form.